The North Central Coast Tawantinsuyu in Peru: Valleys of Chancay and Huaura - Van Dalen Luna, Pieter D. (2011)
Tawantinsuyu included in its maximum expansion throughout the Central Andes, using fferent strategies of dominance for each national group conquered. The region of the central north coast of Peru, held in late periods of the Chancay, features unlike other outlying areas, a slight presence Tawantinsuyu, evidenced by the architecture and ceramics.